2003
DOI: 10.1038/sj.bjc.6600667
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypoxia-dependent 2-nitroimidazole KIN-841 inhibits tumour-specific angiogenesis by blocking production of angiogenic factors

Abstract: Tumour angiogenesis is initiated by angiogenic factors that are produced in large amounts by hypoxic tumour cells. The inhibition of this step may lead to tumour-specific antiangiogenesis because normal tissues are not usually hypoxic. On the other hand, blocking a biological function of endothelial cells is known to result in angiogenic inhibition. To produce a tumour-specific and powerful antiangiogenesis, we determined whether potent angiogenic inhibition could be achieved by inhibiting the production of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Tumor‐induced blood vessel formation was assessed as described previously. ( 23 ) In brief, Millipore chambers (Millipore) were filled with either PBS alone or a suspension of 1.5 × 10 7 LLC cells in PBS with or without 2‐OX and sealed with membrane filters (0.45‐”m pores). Chambers were implanted subcutaneously in dorsal air sacs created surgically by injection of an appropriate volume of air in 7‐week‐old male C57BL/6J mice.…”
mentioning
confidence: 99%
“…Tumor‐induced blood vessel formation was assessed as described previously. ( 23 ) In brief, Millipore chambers (Millipore) were filled with either PBS alone or a suspension of 1.5 × 10 7 LLC cells in PBS with or without 2‐OX and sealed with membrane filters (0.45‐”m pores). Chambers were implanted subcutaneously in dorsal air sacs created surgically by injection of an appropriate volume of air in 7‐week‐old male C57BL/6J mice.…”
mentioning
confidence: 99%
“…[57][58][59] In this section, molecular design and synthesis of several 2-nitroimidazole analogs are reported. [60][61][62][63][64][65][66][67][68] Haloacetylcarbamoyl-2-nitroimidazole analogs have a chiral center, and show antiangiogenetic activity. 8) Methyl including TXs, TX-1863, -1878, -1866, -1879, inhibited angiogenesis (80-100%) at 100 mg/pellet (Fig.…”
Section: Role Of Rigid and Flexible Center On Bio-logical Activity: Cmentioning
confidence: 99%
“…Selective delivery of this drug into the tumour neovascular endothelium may dissociate the desired anti-angiogenic effects from the immunosuppressive effects that unfavourably affect tumour growth (Guba et al 2002). In another study, an attempt was made to inhibit the production of angiogenic factors in hypoxic tumour cells using a novel hypoxia-dependent 2-nitroimidazole, KIN-841, which covalently binds and is cytotoxic to hypoxic tumour cells, and simultaneously disrupt the endothelial cell function using the same agent, to achieve angiogenesis inhibition (Shimamura et al 2003). It was observed that KIN-841 inhibited the proliferation of endothelial cells under normoxia.…”
Section: Vascular Targeting Induced Tumour Endothelial Cell Killingmentioning
confidence: 99%